Aluminium Oxide Thin-Film Based in Vitro Cell-Substrate Sensing Device for Monitoring Proliferation of Myoblast Cells - Kasiviswanathan U.; Balavigneswaran C.K.; Kumar C.; Poddar S.; Jit S.; Sharma N.; Mahto S.K. (My University, 2025)
We demonstrate cell-substrate interaction on aluminium oxide thin-film in metal-insulator-metal structure followed by the change in dielectric characteristics of Al2O3 as a function of progression of cellular growth. The theoretical calculation of the fabricated biosensor reveals that the changes in the intrinsic elemental parameters are mainly attributed to the cell-induced behavioural changes. © 2002-2011 IEEE.